The Effectiveness of Using PhET Simulation on Parabolic Motion Material at Thammasat Wittaya School, Thailand - Mohamad Fikri; Sari, Amalia Nurdina; Jannah, Lutfiah Hafifatul; Hamidong, Sofia; Baheng, Sueda (JURNAL PEMBELAJARAN FISIKA, 2025)
This study aims to analyze the effectiveness of interactive learning media PhET Simulation in improving critical thinking skills and student learning outcomes on parabolic motion material at Thammasat Wittaya Dharmasathan School, Thailand. The method used is an experiment with a quantitative descriptive approach. The research sample was students of class Mattayom 5/1. Data collection techniques were carried out through pre-test and post-test. The results showed an increase in the percentage of student learning completion from 0% in the pre-test to 56.25% in the post-test. N-Gain analysis showed an increase in learning outcomes with a score of 0.52 in the moderate category. The t-test showed a calculated t value > t table (3.65 > 2.131), so H₀ was rejected. This means that there is a significant difference between student learning outcomes before and after using PhET Simulation. Thus, PhET Simulation media is effective in improving students' understanding of physics concepts, especially on parabolic motion material. Keywords: PhET Simulation, learning outcomes, critical thinking skills, parabolic motion, physics learning